2014
DOI: 10.1111/gcb.12499
|View full text |Cite
|
Sign up to set email alerts
|

Body size and activity times mediate mammalian responses to climate change

Abstract: Model predictions of extinction risks from anthropogenic climate change are dire, but still overly simplistic. To reliably predict at-risk species we need to know which species are currently responding, which are not, and what traits are mediating the responses. For mammals, we have yet to identify overarching physiological, behavioral, or biogeographic traits determining species' responses to climate change, but they must exist. To date, 73 mammal species in North America and eight additional species worldwid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(162 citation statements)
references
References 53 publications
(146 reference statements)
8
154
0
Order By: Relevance
“…Equally, palaeontological data provide a broader perspective on the current biodiversity crisis. Specifically, it enables deep time tests of the purported relationships between present day extinction susceptibility and geographical range size 53,54 , latitudinal distribution 55 , niche breadth 56 and body size 57,58 .…”
Section: Resultsmentioning
confidence: 99%
“…Equally, palaeontological data provide a broader perspective on the current biodiversity crisis. Specifically, it enables deep time tests of the purported relationships between present day extinction susceptibility and geographical range size 53,54 , latitudinal distribution 55 , niche breadth 56 and body size 57,58 .…”
Section: Resultsmentioning
confidence: 99%
“…S3). We emphasize, however, that arctic and montane species, including high-altitude endemics, are particularly vulnerable to climate change (30,31) and thus still impacted by natural fragmentation that might prevent distributional shifts in response to altered climate regimes.…”
Section: Significancementioning
confidence: 90%
“…An analysis of mammalian responses to climate change revealed that species that exhibit flexibility in activity times were less likely to respond negatively to climate change [14]. The opportunity for large mammals to shift activity to night, however, may be constrained by factors such as the energetic costs of being active over the cooler night, predation, or night vision ability.…”
Section: Behavioural Adjustmentsmentioning
confidence: 99%
“…Through its effects on life history, morphology, physiology and ecology, body size will influence how well mammals are able to buffer the effects of climate change. Although climate change may compromise larger mammals more than smaller mammals, as it has in the Earth's history [13], it will not influence all species of a given body mass to the same extent, and some species actually may benefit from climate change [14]. Understanding how different species will respond to climate change requires an understanding of their exposure and sensitivity to environmental change, as well as the plasticity available to them to buffer such changes.…”
Section: Introductionmentioning
confidence: 99%